FENOMENA PERJUDIAN BURUNG MERPATI DAERAH RUNGKUT TENGAH - Nasrudin Fadli, Ahmad; Dwi Rahardjo, Ridho (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2021)
This study aims to offer solutions related to the prevalence of pigeon gambling in the Rungkut Tengah area of Surabaya. Through an empirical approach which is sourced from existing data in the field such as interviews and observations. Through this research, researchers offer a way out of the existence of pigeon gambling which is expressly prohibited in statutory regulations. By holding counseling and providing a forum such as an official competition to be able to channel hobbies in raising and caring for pigeons without having to participate in gambling. Law enforcement related to the prevalence of gambling cases that develop in the community certainly makes it difficult for the authorities to eradicate various gambling so that the law appears in line with existing norms. Through the efforts of the government and law enforcement officials, the making of regulations regarding the sanctions imposed by the practice of gambling does not make the public afraid of these threats. This is what makes it necessary to do something new related to efforts to eradicate pigeon gambling in Central Rungkut without having to stop the hobby of pigeon fans in the area, of course. Keywords: gambling; pigeons; solutions Abstrak Penelitian ini bertujuan untuk menawarkan solusi terkait maraknya perjudian burung merpati di wilayah Rungkut Tengah Surabaya. Melalui metode pendekatan secara empiris dimana bersumber dari data yang ada dilapagan seperti wawancara dan observasi. Melalui penelitian ini, peneliti menawarkan jalan keluar dari adanya perjudian burung merpati yang secara tegas dilarang didalam peraturan perundang-undangan. Dengan mengadakan penyuluhan serta memberikan wadah seperti perlombaan resmi untuk dapat menyalurkan hobi dalam memelihara serta merawat burung merpati tanpa harus mengikuti perjudian. Penegakan hukum terkait maraknya kasus perjudian yang berkembang dimasyarakat tentu membuat pihak aparat mengalami kesulitan dalam memberantas berbagai perjudian agar hukum terlihat sejalan dengan norma yang ada. Melalui upaya pemerintah serta aparat penegak hukum dengan dibuatnya aturan mengenai sanksi yang ditimbulkan oleh praktek perjudian tersebut tidak membuat masyarakat takut akan ancaman tersebut. Hal ini yang membuat perlu dilakukannya kebaruan terkait dengan upaya untuk memberantas perjudian burung merpati di Rungkut Tengah tanpa harus menghentikan hobi penggemar burung merpati diwilayah tersebut tentunya.